Fucino palaeolake multiproxy data from F1-F3 core (Holocene - 190 ka) - Mannella, Giorgio; Giaccio, Biagio; Zanchetta, Giovanni; Regattieri, Eleonora; Niespolo, Elizabeth M; Pereira, Alison; Renne, Paul; Nomade, Sébastien; Leicher, Niklas; Perchiazzi, Natale; Wagner, Bernd (Supplement to: Mannella, G et al. (2019): Palaeoenvironmental and palaeohydrological variability of mountain areas in the central Mediterranean region: A 190 ka-long chronicle from the independently dated Fucino palaeolake record (central Italy). Quaternary Science Reviews, 210, 190-210, https://doi.org/10.1016/j.quascirev.2019.02.032, 2019)
Here we present a multi-proxy record from palaeolake Fucino (Abruzzo, Central Italy), acquired during the F1-F3 drilling campaign. This is the first continuous and high-resolution palaeoenvironmental record in the central Mediterranean region continuously spanning over the last two glacial-interglacial cycles and providing an independent chronology. The record consists of a core composite resulting from two parallel and adjacent core series (F1 and F3). Cores were analysed via high resolution XRF scanning and through geochemical, mineralogical and grain-size analyses on discrete samples. Selected XRF elemental counts (Ca, Ti and Zr), Total Nitrogen (TN), Total Organic and Inorganic Carbon (TOC, TIC), X-ray powder diffraction and grain-size data are used to develop proxies for local environmental processes strictly dependent on the hydro-climatic regime of the Central Mediterranean region. The chronology of the record is based on 17 radioisotopically dated tephra layers interbedded within the sedimentary succession. 14C and 40Ar/39Ar age points are interpolated with the bayesian age modelling package Bacon allowing a robust assessment of age uncertainties.
Keywords: Age model; Apennines; Bayesian; centennial; Central; change; Eemian; environmental; F1; F3; Fucino; Holocene; independent; Italy; Lake; Mediterranean; millennial; MIS 1; MIS 2; MIS 3; MIS 4; MIS 5; MIS 6; multiproxy; orbital; Saalian; Tephra; Weichselian; XRF